Two new species and two new combinations within Paleosepharia (Coleoptera, Chrysomelidae, Galerucinae) from China - Chuan Feng; Xingke Yang; Siqin Ge (ZooKeys)
In this study, two new species of the leaf-beetle genus Paleosepharia Laboissière, 1936 from China are described: P. subrubra Feng, Yang & Ge, sp. nov. and P. emeiensis Feng, Yang & Ge, sp. nov. Meanwhile, Paleosepharia truncata Laboissière, 1936 is first recorded for China. Additionally, Monolepta bicavipennis Chen, 1942 and Monolepta quadricavata Chen, 1976 are redescribed and proposed as new combinations under Paleosepharia. A key to the Chinese species of Paleosepharia is also provided.